Aksesibilitas Objek Wisata Bagi Wisatawan Penyandang Disabilitas di Kota Bandung - Herdiana, Dian; Siti Widharetno, Mursalim (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
Abstract The tourism destination in Bandung city is aimed inclusively at all groups of tourists, but in practice, there is limited accessibility experienced by tourists with disabilities which results in reduced ease, security, and comfort in conducting tourist activities in Bandung city. On this basis, this study aims to explain the problem of accessibility for tourists with disabilities in Bandung city and what solutions are offered to overcome these problems. The research method used is the descriptive research method with a qualitative approach. The results revealed that the tourist area in Bandung city can not be said to be accessible for tourists with disabilities. This can be seen from the lack of existing infrastructure in the attractions area and the lack of other supporting infrastructure aimed at supporting tourism activities carried out by tourists with disabilities. Efforts should be made to realize tourism that is accessible to tourists with disabilities by realizing the shared commitment by Bandung city government and tourism management bodies to create policy instruments that clearly and detailly regulate tourism development that is accommodating to the needs of tourists with disabilities. The policy should substantively regulate the provision of tourism facilities for tourists with disabilities in Bandung city.